2020
DOI: 10.1038/s41598-020-60125-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific Health complaints and self-rated health in pre-adolescents; impact on primary health care use

Abstract: The objective of the present study was to explore past and future primary health care use in preadolescents reporting frequent non-specific health complaints or a low self-rated health compared to that of preadolescents with no frequent health complaints or with good self-rated health. The study was conducted as a cohort study based within the Danish National Birth Cohort (1996-2002). Information on non-specific health complaints and self-rated health was obtained by an 11-year follow-up questionnaire. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“… 48 One study performed on the same population as in this study, found higher primary health care use in children with frequent health complaints and low SAH. 31 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 48 One study performed on the same population as in this study, found higher primary health care use in children with frequent health complaints and low SAH. 31 …”
Section: Discussionmentioning
confidence: 99%
“…For both somatic and mental complaints, the response options were: almost every day; more than once a week; almost every week; more than once a month; almost every month; or, rarely or never. As in previous research on this cohort, 31 the outcome was reporting the presence of daily and almost every day health complaints. This symptom checklist has previously been found to have high reliability and validity.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…They concluded that children with frequent non-specific complaints and low self-assessment use primary care services more often than children without complaints or with good self-assessment. They also emphasize that the increase in non-specific complaints is a global phenomenon and requires early interventions to prevent morbidities and an increase in health costs 16 . Considering the results of the present study, the structure for monitoring and prevention actions is an urgent necessity.…”
Section: Discussionmentioning
confidence: 99%